1994
DOI: 10.1084/jem.179.1.145
|View full text |Cite
|
Sign up to set email alerts
|

The T cell receptor repertoire of CD4-8+ thymocytes is altered by overexpression of the BCL-2 protooncogene in the thymus.

Abstract: SummaryThe bcl-2 gene encodes an intracellular, membrane-associated protein that protects immature cortical thymocytes from a wide variety of apoptotic stimuli, including glucocorticoids, radiation, and anti-CD3 treatment. Since cortical thymocytes are the primary target cells for thymic positive and negative selection processes, and since these processes are associated with cell death, we evaluated the role of bcl-2 in T cell development in two ways. In the first approach, transgenic mice expressing high leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 51 publications
1
36
0
Order By: Relevance
“…Mice deficient in Bcl-2 showed a gradual disappearance of T (and B) cells after the second week of life (16,17). These results suggest that Bcl-2 may protect thymocytes undergoing positive selection from apoptotic stimuli (18,19). In IL-7R␣ Ϫ/Ϫ and common ␥-chain Ϫ/Ϫ mice, endogenous Bcl-2 expression in thymocytes is greatly reduced, and forced expression of human Bcl-2 as a transgene rescues T lymphopoiesis, indicating the importance of Bcl-2-mediated survival signals for T cell development (20,21).…”
Section: Overexpression Of Bcl-2 Differentially Restores Development Ofmentioning
confidence: 61%
See 1 more Smart Citation
“…Mice deficient in Bcl-2 showed a gradual disappearance of T (and B) cells after the second week of life (16,17). These results suggest that Bcl-2 may protect thymocytes undergoing positive selection from apoptotic stimuli (18,19). In IL-7R␣ Ϫ/Ϫ and common ␥-chain Ϫ/Ϫ mice, endogenous Bcl-2 expression in thymocytes is greatly reduced, and forced expression of human Bcl-2 as a transgene rescues T lymphopoiesis, indicating the importance of Bcl-2-mediated survival signals for T cell development (20,21).…”
Section: Overexpression Of Bcl-2 Differentially Restores Development Ofmentioning
confidence: 61%
“…Because Bcl-2 is also expressed in SP thymocytes (12)(13)(14)(15)(16)(17), it is possible that engagement of MHC class I-peptide with TCR induces IRF-1 which subsequently up-regulates cell survival signals involving Bcl-2 in SP thymocytes. Although Bcl-2 may augment positive selection (18,19), up-regulation of this molecule alone does not promote thymocyte differentiation (18). It is possible that the prolonged survival induced by Bcl-2 may give these cells "an appropriate duration" to obtain sufficient signals necessary for positive selection.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, thymocytes of Bcl-2 or Bcl-x L Tg mice show resistance to deletion induced in vivo by anti-CD3 Ab (33,34). Nevertheless, it has been reported that the negative selection of thymocytes, induced by endogenous superantigen or by H-Y Ag in H-Y Tg model, is normal in these mice (33)(34)(35). However, in contrast to these reports, Strasser (36) also reported that Tg expression of bcl-2 Tg mice diminished self Ag-reactive H-Y Tg T cells.…”
Section: Discussionmentioning
confidence: 98%
“…Increased numbers of CD8 cells have been observed in several other transgenic mice. For example, Bcl2-or TOX-overexpressing transgenic mice show an accumulation of mature CD8 thymocytes for different reasons (36,37). It is possible that extra HBP1 molecules accelerate the rate of commitment toward the CD8 lineage at the expense of CD4 SP cell production.…”
Section: Discussionmentioning
confidence: 99%